2011
DOI: 10.1007/s00421-011-2073-2
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity endurance training improves adiponectin mRNA and plasma concentrations

Abstract: Adiponectin is an anti-inflammatory protein that reduced in obesity. Exercise training may reduce the adipose tissue (AT), although it is not well known whether exercise-induced change in AT, increases the adiponectin mRNA expression and plasma concentrations or not; therefore, the purpose of this study was to investigate the adiponectin mRNA and plasma concentrations in middle-aged men after 12 weeks high-intensity exercise training and after a week detraining. Sixteen sedentary overweight and obese middle-ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 45 publications
3
64
0
1
Order By: Relevance
“…After the training program, the serum adiponectin concentrations were increased in both groups 31 . long-term training (≥ 12 weeks) -Moghadasi et al 12 investigated the mrNA adiponectin and plasma concentrations in middleaged overweighed and obese men after high-intensity physical training of 12 weeks (4 d/w) with 75-80% of individual maximum oxygen consumption for 45 min and after one week of detraining. The results showed that the plasma adiponectin concentrations increased after training in the experimental group compared with the control group (p< 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the training program, the serum adiponectin concentrations were increased in both groups 31 . long-term training (≥ 12 weeks) -Moghadasi et al 12 investigated the mrNA adiponectin and plasma concentrations in middleaged overweighed and obese men after high-intensity physical training of 12 weeks (4 d/w) with 75-80% of individual maximum oxygen consumption for 45 min and after one week of detraining. The results showed that the plasma adiponectin concentrations increased after training in the experimental group compared with the control group (p< 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Tere are some reports that exercise may lead to increase of the adiponectin levels 12,13 , while others did not present any alteration in the adiponectin concentrations 14,15 . little is known about the alterations of the adiponectin levels during puberty and even less information about the detraining role after physical training on physical fitness as well as about the levels of adiponectin in the blood plasma of obese children.…”
mentioning
confidence: 94%
“…Thus far, however, there has been no consensus as to the effect of exercise on serum adiponectin concentration, which has been reported to decrease 22,23) , increase 5,6,24) , and remain unchanged 7,25) with exercise.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…Several studies have shown significant increases in serum adiponectin concentration after high-intensity training 5,6,24) . However, in those studies, increases in adiponectin level were almost always accompanied by loss of fat mass 5,6,24) .…”
Section: Conflict Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation